Issues of minority settlers and minorities in Canada as portrayed in Canadian literature - Pachl, Ivan (Univerzita Pardubice, 2010)
This thesis deals with issues of immigrant life in early twentieth century Canada and the way it is portrayed English-language literature. The thesis concentrates on the Mennonite and the Jewish immigrant communities and their depiction in the novels of two Canadian writers - Rudy Wiebe's Peace Shall Destroy Many and Adele Wiseman's The Sacrifice. An integral part of the thesis an overview of early English-language records of immigrant life in Canada. Chapters dealing with the historic backgrounds to both the Mennonite and Jewish communities are also included. The main core of the thesis deals with comparing both aforementioned novels - the style in which they are written and the way in which they relate to actual events during the process of settling Canada. Secondary literature analysing historical events pertaining to both communities described by the respective novels is also used to present as balanced a view of the period as possible.
Problematika menšin osadníků v Kanadě a jejich vylíčení v kanadské literatuře
Keywords: imigranti; mennonité; židé; konflikty; osadníci; Kanada; immigrants; Mennonite; Jewish; conflicts; settlers; Canada